Preparation of cyclic imides from alkene-tethered amides: application of homogeneous Cu(ii) catalytic systems. Issue 13 (21st February 2020) - Liu, Zhenghui; Wang, Peng; Ou, Hualin; Yan, Zhenzhong; Chen, Suqing; Tan, Xingxing; Yu, Dongkun; Zhao, Xinhui; Mu, Tiancheng
Abstract : A catalytic system comprising Cu(ii ) and a nitrogen-based ligand for the oxygenation and cyclization of alkene-tethered amides. Abstract : A Cu-based homogeneous catalytic system was proposed for the preparation of imides from alkene-tethered amides. Here, O2 acted as a terminal oxidant and a cheap and easily available oxygen source. The cleavage of CC bonds and the formation of C–N bonds were catalyzed by Cu(ii ) salts with proper nitrogen-containing ligands under 100 °C. The synthesis approach has potential applications in pharmaceutical syntheses. Moreover, scaled-up experiments confirmed the practical applicability.